المحضرة بطريقة التحلل الكيميائي الحراري(ZnO:Bi) الخصائص التركيبية والبصرية لاغشية - اكرم عباس اسراء; فاضل حبوبي نادر (مجلة كلية التربية, 2020)
In this research , the study of the structure properties and some properties optical properties of zinc oxide (ZnO) thin films prepared by the chemical spray pyrolysis technique. These thin films were deposited on the glass substrates heated at (400 OC) and the overage hickness was about ( 300 nm). The effect of Bismuth doing with different ratios (1,2,3,4,%) on the structural and optical properties of the Zno films has been studied.The (XRD) results showed that all the prepared films have polycrystalline single phase and the structure was hexagonal wurtzite with a preferred orientation along (002) plane.The average grain size decreased from (45nm) to (12 nm) by in increasing the doping percentage also, the (AFM) image show different surface morphology for the prepared films.The absorbance and transmittance spectra have been recorded in the wavelength range (380-900 nm) in order to study the optical properties. It was found that the maximum transmittance inereased to (83%) at (ZnO) pure, and the optical energy gap for allowed direct transition electronic (3.3eV) for ZnO, while the increase in doping percentadage led to decrease in the value of the energy gap and for maximum doping (4%) it reach (3.0 eV), on contrary with urbach energy which increase as the doping percentage increase where equal (135 meV) for (ZnO) and when (4%) it reaches (333 meV).